Relationship Between Premenstrual Syndrome (Pms) And Appetite In Female Medical Students At Sam Ratulangi University - Enmilia Banuarsih Raule; Ivonny Melinda Sapulete; Joice Nancy Ansje Engka (Riviera Publishing, 2025)
Premenstrual Syndrome (PMS) is conditions that affect part big Woman age reproduction, with symptoms vary? including change lust eating. Hormonal changes that occur in the luteal phase of the menstrual cycle menstruation can influence regulation lust eating and pattern consumption food. Research This aiming For analyze connection between PMS and lust eating at college students Faculty Sam Ratulangi University Medical School Class of 2024. Research This aiming For identify connection between PMS symptoms with change lust Eat as well as factors that influence it. Research This use design observational analytic with cross-sectional approach. Research sample a total of 138 female students were selected through purposive sampling technique. Data collected use Simplified Nutritional Appetite Questionnaire (SNAQ) questionnaire for measure lust eating and the Shortened Premenstrual Assessment Form (SPAF) for measure PMS symptoms. Data analysis was performed with the Spearman correlation test with level significance 0.05. Research results show that part big respondents (99.3%) experienced PMS symptoms with level severity varies. As many as 81.2% of respondents own lust eat well? during PMS, while the other 18.8% report lust undereating. Analysis?? correlation show existence connection positive weak between PMS and lust eating (r = 0.338, p < 0.001), which indicates that the more critical PMS symptoms, increasingly increase lust Eat respondents. Findings This confirm importance understanding more carry on about change physiological and psychological things that happen during PMS as well the impact to pattern eating.